Some questions of non-governmental organizations in the Republic of Kazakhstan: their role in the formation of energy policy (Journal of actual problems of jurisprudence, 2018)
The article discusses the status and direction of development of the NGO sector in the Republic of Kazakhstan and its role in the development of a democratic society. It noted the relevance and importance of the role of non-governmental organizations, both in the policies of individual states and internationally. The interaction of the non-governmental sector and the state, the effect of this interaction on the development of society. The paper notes the lack of interaction of state bodies and non-governmental organizations in the implementation of the energy security of NGO projects. The possible ways of activities and the participation of NGOs in the mechanism of control of the company in the production and transportation of energy are offered, in particular, to develop recommendations to improve the responsibility of energy producers for environmental pollution, the establishment of an independent mechanism for monitoring compliance with environmental legislation.Key words: non-governmental sector, non-governmental organizations, the environment, the state.